Recent advances on materials for lithium-ion batteries - Barbosa, João C. (2021)
Environmental issues related to energy consumption are mainly associated with the strong dependence on fossil fuels. To solve these issues, renewable energy sources systems have been developed as well as advanced energy storage systems. Batteries are the main storage system related to mobility, and they are applied in devices such as laptops, cell phones, and electric vehicles. Lithium-ion batteries (LIBs) are the most used battery system based on their high specific capacity, long cycle life, and no memory effects. This rapidly evolving field urges for a systematic comparative compilation of the most recent developments on battery technology in order to keep up with the growing number of materials, strategies, and battery performance data, allowing the design of future developments in the field. Thus, this review focuses on the different materials recently developed for the different battery components—anode, cathode, and separator/electrolyte—in order to further improve LIB systems. Moreover, solid polymer electrolytes (SPE) for LIBs are also highlighted. Together with the study of new advanced materials, materials modification by doping or synthesis, the combination of different materials, fillers addition, size manipulation, or the use of high ionic conductor materials are also presented as effective methods to enhance the electrochemical properties of LIBs. Finally, it is also shown that the development of advanced materials is not only focused on improving efficiency but also on the application of more environmentally friendly materials.